Serum Hepatocyte Growth Factor Concentration Correlates with Albuminuria in Individuals with Optimal Blood Pressure and Untreated Arterial Hypertension - Margareta Fistrek Prlic; Ivana Vukovic Brinar; Jelena Kos; Zivka Dika; Ema Ivandic; Mirjana Fucek; Bojan Jelakovic (Biomedicines, 2024)
Background/Objectives: Hepatocyte growth factor (HGF) is a protective factor against acute renal injury and chronic renal fibrosis. A positive correlation between HGF and blood pressure (BP) has been established. This study aimed to determine the association between serum HGF concentration and albuminuria in subjects with optimal blood pressure (OBP) and untreated arterial hypertension (UAH), as well as its association with BP levels, serum glucose levels, and inflammatory markers. Methods: Data from 563 subjects were analyzed. Albuminuria was normalized to urine creatinine and expressed as the albumin/creatinine ratio (ACR). HGF, serum glucose, C-reactive protein, and blood leucocyte counts were measured. BP was measured and subjects were divided into optimal blood pressure (BP < 120/80 mmHg, N = 295) and untreated arterial hypertension (BP > 140/90 mmHg, N = 268) groups. Results: The subjects with UAH were significantly older and had higher values of body mass index, waist circumference, serum total and LDL cholesterol levels, triglyceride levels, fasting glucose levels, and ACR (all p < 0.001). A significant positive correlation was found between serum HGF concentration and ACR in both groups. There was no difference or correlation between HGF and BP or inflammatory markers in either group. The multivariate regression analysis identified serum HGF concentration as a strong predictor of ACR increase (Beta = 0.376, p < 0.001). Conclusion: This study found that serum HGF concentration is associated with albuminuria not only in individuals with untreated arterial hypertension, but also in those with optimal blood pressure. The results suggest that serum HGF is an independent predictor of ACR increase in both groups.